RT-PCR diagnosis of invasive Candida albicans strain predominant among a private school in Kirkuk City - Tawfeeq , Asal Aziz (GSC Biological and Pharmaceutical Sciences, 2020)
This work was carried out to investigate the incidence of the invasive Candida albicans fungus in oral swabs collected from a private primary school and to confirm its invasiveness by RT-PCR. Accordingly, the total of (368) students in the age range of (7-12) years from both sexes was orally examined for the incidence of Candida albicans from October 2019 to March 2020. Wet oral swabs were directly cultured on Sabouraud agar medium, and positive cultures were examined microbiologically. Results of Gram's staining revealed the isolation of the invasive Candida albicans confirmed by the germ tube test. This fungus was significantly (P<0.05) prevalent in most of the school students, where males were more affected (64.53%) than female students (35.47%) across all age groups. Moreover, the molecular analysis of the isolated fungal strains confirmed the invasiveness of the isolates.